Polyoxometalates as Catalysts for Biomass Conversion: Properties, Applications, and Regenerability - Haryo P. Winoto; Rezky O. Anggaswara; Dian H. Wahyudi; Rino R. Mukti; Veinardi Suendo; Ismunandar Ismunandar (Directorate for Research and Community Services, Institut Teknologi Bandung, 2026)
Polyoxometalates (POMs) have emerged as exceptionally versatile catalysts for green chemical reactions, demonstrating significant potential in the sustainable valorization of biomass. Their tunable Brønsted/Lewis acidity and redox properties enable a broad range of chemical transformations, offering remarkable flexibility in process design. This mini review provides a summary of recent advances in the thermocatalytic conversion of biomass using POMs, addressing their utilization as both homogeneous and heterogeneous catalysts. Key reaction pathways, including solvolysis, oxidation, esterification, and condensation, are highlighted as fundamental processes in biomass valorization. A central focus is placed on the crucial challenge of catalyst regenerability and stability, examining strategies to ensure the long-term viability and economic feasibility of these systems while facing the apparent low-temperature stability challenge of POMs. Finally, this review synthesizes current regeneration methods and presents a forward-looking perspective on the future challenges and opportunities in the field of biomass conversion catalyzed by polyoxometalates.